Impact of Disclosing Fat Content on Consumer Sensory Evaluation of Ground Beef From a Similar Source - K. R. Lybarger; K. M. Harr; E. S. Beyer; K. J. Farmer; S. G. Davis; M. D. Chao; J. L. Vipham; M. D. Zumbaugh; T. G. O'Quinn (Kansas Agricultural Experiment Station Research Reports, 2022)
Objective:The objective of this study was to determine the impact of providing consumers with information regarding the fat content of ground beef on the consumer’s eating experience. Study Description:Ground beef chubs that were 80% lean/20% fat (n= 15/panel type) were obtained, and 0.25-lb patties were fabricated from the chubs. Chubs were assigned randomly to panels. Panelists received samples labeled as the following: 90% lean/10% fat (90/10), 80% lean/20% fat (80/20), 73% lean/27% fat (73/27), lean, extra lean, and one sample with no information given (NONE). Samples were evaluated by consumers (n = 105), who were provided information regarding treatment labels prior to evaluation, on 0- to 100-point line scales for tenderness, juiciness, flavor, texture overall liking, and purchasing intent. Consumers also rated each trait as acceptable or unacceptable. Ground beef with 90/10, 80/20, and 73/27 labels resulted in a large increase (P<0.05) in consumer ratings for tenderness, flavor, and overall liking. The Bottom Line:Presenting information regarding fat content to consumers influenced perceived palatability of ground beef. Today’s consumers are paying closer attention to labeling statements than in the past. Results from this study support this trend, indicating consumers’ eating experiences are affected by the fat content labeling found on ground beef packages. Ground beef marketing decisions should consider the information incorporated on packaging, including fat content, as there is an impact on consumers’ palatability experience.
Keywords: ground beef; palatability; fat content